Production of ultra-deep sulfur-free diesels using a sustainable catalytic system based on UiO-66(Zr)1. Issue 72 (18th September 2015) - Granadeiro, Carlos M.; Ribeiro, Susana O.; Karmaoui, Mohamed; Valença, Rita; Ribeiro, Jorge C.; de Castro, Baltazar; Cunha-Silva, Luís; Balula, Salete S.
<x xml:space="preserve">Abstract</x> The porous metal–organic framework UiO-66(Zr) is a remarkable and highly efficient heterogeneous catalyst for the production of sulfur-free diesels.